2011
DOI: 10.1007/s10526-011-9348-8
|View full text |Cite
|
Sign up to set email alerts
|

Transmission of Metarhizium brunneum conidia between male and female Anoplophora glabripennis adults

Abstract: Transmission of conidia between mates of the Asian longhorned beetle, Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambycidae), was studied using two isolates of the entomopathogenic fungus Metarhizium brunneum Petch (Hypocreales: Clavicipitaceae) (formerly M. anisopliae). After one beetle was inoculated and caged with a mate for 6 h, conidia were rinsed off each beetle using Tween-80 and pentane to count conidia transferred. Treated males transmitted more conidia to females than treated females trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 24 publications
0
17
0
1
Order By: Relevance
“…Higher numbers of conidia were apparently picked up by each single beetle while walking over the dry fungal formulation, which may point to be suitability of the dry formulation and the higher concentration used. Peng et al (2011) reported similar findings from exposing the ventral surfaces of Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambicidae) beetles to Metarhizium brunneum: a method comparable to what may happen when insects walk over a fungal band on a tree. Since many conidia are lost to the environment, we hypothesize that through fungal auto-dissemination devices beetles can spread some conidia as they walk over the branches, potentially inoculating other beetles of either sex.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Higher numbers of conidia were apparently picked up by each single beetle while walking over the dry fungal formulation, which may point to be suitability of the dry formulation and the higher concentration used. Peng et al (2011) reported similar findings from exposing the ventral surfaces of Anoplophora glabripennis (Motschulsky) (Coleoptera: Cerambicidae) beetles to Metarhizium brunneum: a method comparable to what may happen when insects walk over a fungal band on a tree. Since many conidia are lost to the environment, we hypothesize that through fungal auto-dissemination devices beetles can spread some conidia as they walk over the branches, potentially inoculating other beetles of either sex.…”
Section: Discussionmentioning
confidence: 69%
“…), Lymantria dispar L., Anoplophora glabripennis (Motschlsky), Monochamus sp. (Draganova et al, 2013;Peng et al, 2011;Sevim et al, 2010) and others.…”
Section: Discussionmentioning
confidence: 98%
“…Fungal bands were stored for up to 1 yr at 4ЊC before use. Conidial concentration per unit area of band material was quantiÞed as in Peng et al (2011) by blending 5-by 5-cm sections of fungal bands in 0.2% Tween-80, Þltering the suspension through two layers of cheesecloth, rinsing the cheesecloth with water to remove conidia, vortexing the Þltrate, and counting conidia with a hemocytometer. To quantify conidial viability, the suspension was diluted with water to 1 ϫ 10 7 conidia/ml and a 1-ml aliquot was spread onto each of three 90-mm diameter petri dishes containing Sabouraud dextrose agar plus yeast extract (Inglis et al 2012) with 0.1% gentamicin added before autoclaving to control growth of contaminants.…”
Section: Methodsmentioning
confidence: 99%
“…The horizontal transmission between different hosts of B. bassiana (García-Munguia et al 2011), Metarhizium anisopliae (Metsch.) Sorokin (Peng et al 2011) and Isaria fumosorosea (= Paecilomyces fumosoroseus) (Wize) Brawn & Smith (Avery et al 2010) has already been shown. However this is first attempt at assessing the transmission of B. bassiana between the larvae of D. saccharalis.…”
Section: Introductionmentioning
confidence: 95%